Biochemical characterization and substrate specificity of jojoba fatty acyl-CoA reductase and jojoba wax synthase. (August 2016) - Miklaszewska, Magdalena; Banaś, Antoni
Highlights: Fatty acyl-CoA reductases (FAR) and wax synthases (WS) catalyze the final step of wax esters formation. Jojoba FAR and WS genes were heterologously expressed in Saccharomyces cerevisiae . Detailed characterization of in vitro substrate specificity of jojoba FAR and WS was performed. Jojoba FAR produced mainly 18:0-OH, followed by 20:1-OH and 22:1-OH. Jojoba WS appeared to be most suitable for synthesis of C30, C32 and C34 wax esters from certain combinations of substrates. Abstract: Wax esters are used in industry for production of lubricants, pharmaceuticals and cosmetics. The only natural source of wax esters is jojoba oil. A much wider variety of industrial wax esters-containing oils can be generated through genetic engineering. Biotechnological production of tailor-made wax esters requires, however, a detailed substrate specificity of fatty acyl-CoA reductases (FAR) and wax synthases (WS), the two enzymes involved in wax esters synthesis. In this study we have successfully characterized the substrate specificity of jojoba FAR and jojoba WS. The genes encoding both enzymes were expressed heterologously in Saccharomyces cerevisiae and the activity of tested enzymes was confirmed by in vivo studies and in vitro assays using microsomal preparations from transgenic yeast. Jojoba FAR exhibited the highest in vitro activity toward 18:0-CoA followed by 20:1-CoA and 22:1-CoA. The activity toward other 11 tested acyl-CoAs was low or undetectable as with 18:2-CoA and 18:3-CoA. In assays characterizing jojoba WS combinations of 17 fatty alcohols with 14 acyl-CoAs were tested. The enzyme displayed the highest activity toward 14:0-CoA and 16:0-CoA in combination with C16-C20 alcohols as well as toward C18 acyl-CoAs in combination with C12-C16 alcohols. 20:1-CoA was efficiently utilized in combination with most of the tested alcohols.